2018
DOI: 10.3390/md16100394
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Antioxidant Properties of Acid- and Pepsin-Soluble Collagens from the Scales of Miiuy Croaker (Miichthys Miiuy)

Abstract: In this report, acid-soluble collagen (ASC-MC) and pepsin-soluble collagen (PSC-MC) were extracted from the scales of miiuy croaker (Miichthys miiuy) with yields of 0.64 ± 0.07% and 3.87 ± 0.15% of dry weight basis, respectively. ASC-MC and PSC-MC had glycine as the major amino acid with the contents of 341.8 ± 4.2 and 344.5 ± 3.2 residues/1000 residues, respectively. ASC-MC and PSC-MC had lower denaturation temperatures (32.2 °C and 29.0 °C for ASC-MC and PSC-MC, respectively) compared to mammalian collagen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 61 publications
(145 reference statements)
9
36
1
Order By: Relevance
“…The amide III bands represent the combination of the C–N stretching vibration and the N–H bending vibration [56]. The amide III absorption bands of ASC and PSC appeared at 1242.10 cm −1 and 1240.17 cm −1 respectively, which is consistent with previous studies [41].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The amide III bands represent the combination of the C–N stretching vibration and the N–H bending vibration [56]. The amide III absorption bands of ASC and PSC appeared at 1242.10 cm −1 and 1240.17 cm −1 respectively, which is consistent with previous studies [41].…”
Section: Resultssupporting
confidence: 90%
“…Each peak in the FTIR spectrums corresponds to the vibration of functional groups in the molecule [55]. The secondary structure of collagen is closely related to different types of hydrogen bonds [56]. By analyzing the FTIR spectrum of ASC and PSC, the different effects of the two extraction methods on the secondary structure of collagen were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows that the amide A wavenumbers of STB-C (3329.5 cm −1 ) and STB-G (3354.2 cm −1 ) indicate that some N–H groups in STB-G and STB-C contributed to the formation of hydrogen bonds, and the degree of hydrogen bonding in STB-C was more than that of STB-G. The amide B band is related to asymmetric stretch vibrations of –NH3+ and =C–H, and the shift of amide B to a higher wavenumber is associated with an increase in free NH–NH3+ groups from both lysine residues and the N -terminus [5,14]. The wavenumbers of the amide B band of STB-C and STB-G were found at 2936.1 cm −1 and 2932.8 cm −1 , respectively, indicating STB-C had fewer free –NH3+ groups than STB-G.…”
Section: Resultsmentioning
confidence: 99%
“…A lower wavenumber of amide A suggested more hydrogen bonding by N-H groups [25]. The amide A wavenumbers of acid-soluble collagen from the scales of miiuy croaker (M. miiuy) were in 3415 cm −1 , indicating that the hydrogen-bonding numbers of collagen from A. molpadioides were less than that of collagen from M. miiuy [26]. The amide B band corresponded to an asymmetric stretch vibration of -NH 3 + and =C-H, and an increase of free -NH 3 + groups would result in a higher wavenumber [2,8,25].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…Generally, the pIs of collagens from different organisms are different due to differences in their amino acid compositions. It has been reported that the pI of collagen is always between pH 6.0 to 9.0 [29], such as the collagen from the tilapia skin (6.42) [30], the brown-banded bamboo shark (6.21) [31], the scales of the Miiuy Croaker (6.81) [26], and the seabass (6.46) [32]. The lower pI demonstrates that there are more acidic amino acids in collagen from A. molpadioides, especially glutamic acid, which was also proved by the amino acid analysis in Table 1.…”
Section: Zeta Potentialmentioning
confidence: 99%